2019
DOI: 10.1111/iju.14015
|View full text |Cite
|
Sign up to set email alerts
|

Potential of hyperbaric oxygen in urological diseases

Abstract: Abbreviations & Acronyms AKI = acute kidney injury Alum = aluminium potassium sulfate ATA = atmosphere absolute CR = complete response CRPC = castration-resistant prostate cancer DC = dystrophic calcification EMT = epithelial-tomesenchymal transition FG = Fournier gangrene FGSI = Fournier Gangrene Severity Index HA = hyaluronic acid HBO = hyperbaric oxygen HIC = Hunner type interstitial cystitis IC/PBS = interstitial cystitis/painful bladder syndrome NHIC = non-Hunner type interstitial cystitis PR = partial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
0
10
0
1
Order By: Relevance
“…Hyperbaric oxygen therapy can increase blood oxygen content and oxygen partial pressure and improve the state of the whole-body organs. It can be used to treat infertility, acute kidney injury, and wound nonunion of malignant tumor [ 169 ]. Studies have shown that hyperbaric oxygen therapy can improve uterine hemodynamics and ER, improve ovum quality, and improve the reproductive capacity of infertile patients [ 170 , 171 ].…”
Section: Overview Of Other Cam In the Treatment Of Infertilitymentioning
confidence: 99%
“…Hyperbaric oxygen therapy can increase blood oxygen content and oxygen partial pressure and improve the state of the whole-body organs. It can be used to treat infertility, acute kidney injury, and wound nonunion of malignant tumor [ 169 ]. Studies have shown that hyperbaric oxygen therapy can improve uterine hemodynamics and ER, improve ovum quality, and improve the reproductive capacity of infertile patients [ 170 , 171 ].…”
Section: Overview Of Other Cam In the Treatment Of Infertilitymentioning
confidence: 99%
“…Mitochondria, endoplasmic reticulum (ER), peroxisomes, several oxidase enzymes, and phospholipid metabolism can generate reactive oxygen species (ROS), both free radicals and nonradical species. Hydrogen peroxide (H 2 O 2 ) is the main ROS produced in wounds by NADPH oxidase (NOX), which acts as a chemotactic signal in the first minutes after wounding [143]. Beside H 2 O 2 , NOX can generate anion superoxide (O •_…”
Section: Oxygen Metabolism and Wound Healing Processmentioning
confidence: 99%
“…Indien een radiatiecystitis oorzaak is van persisterende hematurie is behandeling met hyperbare zuurstoftherapie succesvol bij 50-80% van de patiënten [40,41].…”
Section: Hematurieunclassified